Methods to Reduce Energy and Polymer Consumption for Fused Filament Fabrication 3D Printing - Owen Harding (Polymers, 2023)
Fused Filament Fabrication (FFF) 3D printing is an additive technology used to manufacture parts. Used in the engineering industry for prototyping polymetric parts, this disruptive technology has been adopted commercially and there are affordable printers on the market that allow for at-home printing. This paper examines six methods of reducing the energy and material consumption of 3D printing. Using different commercial printers, each approach was investigated experimentally, and the potential savings were quantified. The modification most effective at reducing energy consumption was the hot-end insulation, with savings of 33.8–30.63%, followed by the sealed enclosure, yielding an average power reduction of 18%. For material, the most influential change was noted using ‘lightning infill’, reducing material consumption by 51%. The methodology includes a combined energy- and material-saving approach in the production of a referenceable ‘Utah Teapot’ sample object. Using combined techniques on the Utah Teapot print, the material consumption was reduced by values between 55.8% and 56.4%, and power consumption was reduced by 29% to 38%. The implementation of a data-logging system allowed us to identify significant thermal management and material usage opportunities to minimise power consumption, providing solutions for a more positive impact on the sustainable manufacturing of 3D printed parts.